Asian American Religions: The Making and Remaking of Borders and Boundaries - Carnes, Tony (Religion, Race, and Ethnicity, 2004)
Asian American Religions brings together some of the most current research on Asian American religions from a social science perspective. The volume focuses on religion in Asian American communities in New York, Houston, Los Angeles, and the Silicon Valley/Bay Area, and it includes a current demographic overview of the various Asian populations across the United States. It also provides information on current trends, such as that Filipino and Korean Americans are the most religiously observant people in America, that over 60 percent of Asian Americans who have a religious identification are Ch